Use of exosomes containing polydeoxyribonucleotide (PDRN) in facial aesthetics. Clinical case report (Research, Society and Development, 2025)
The search for effective and regenerative aesthetic treatments has driven the use of exosomes in dermatological procedures. This study aims to present a case report demonstrating the application and results of the use of exosomes containing PDRN in facial aesthetics. A patient underwent microneedling associated with the application of exosomes with PDRN for facial rejuvenation. Three intervention sessions were performed at 30-day intervals, using a standardized intradermotherapy protocol. The results showed improvement in skin quality, with increased vitality, reduction of fine lines, and more uniform texture. The study suggests that PDRN-containing exosomes represent a promising strategy in regenerative aesthetics, although further studies are needed to consolidate their clinical efficacy.